Direct transport to PCI-capable hospitals after out-of-hospital cardiac arrest in New Zealand: Inequities and outcomes. (September 2019) - Dicker, Bridget; Todd, Verity F.; Tunnage, Bronwyn; Swain, Andy; Smith, Tony; Howie, Graham
Abstract: Background: It is widely accepted that survival from OHCA may be improved through direct transfer of patients to hospitals with percutaneous coronary intervention (PCI) capability. However, within the New Zealand healthcare system there is limited evidence available to support this. We aimed to compare patient characteristics and outcomes following an out-of-hospital cardiac arrest between those patients transported to hospitals with or without PCI-capability within New Zealand. Method: A retrospective cohort study was conducted using data from the St John New Zealand OHCA registry for adults treated for an out-of-hospital cardiac arrest of presumed cardiac aetiology between 1 October 2013 and 31 October 2018. Population characteristics were investigated using a Chi-Square analysis. Binary logistic regression modelling was used to investigate outcome differences in survival at 30 days post-event according to receiving hospital PCI-capability. Results: The study included 1750 patients who were transported to hospital following an OHCA. A significantly lower proportion of patients over 65 years (49.9%) were conveyed to hospitals with PCI-capability compared to younger aged patients (15–44 years (52.1%) and 45–64 years (59.7%) (p < 0.001). When ethnic groups were compared, Māori (32.9%) had the lowest proportion transported to PCI-capable hospitals, followed by European (55.6%) then Pacific Peoples (86.2%) (p < 0.001). A lower proportion of patients located rurally (34.7%) were transported to hospitals with PCI-capability compared to patients in an urban location (59.1%) (p < 0.001). Thirty-day survival was higher in patients transported to hospitals with PCI-capability (adjusted OR 1.285, 95%CI (1.01–1.63), p = 0.04). Conclusions: Patient characteristic differences indicate that inequities in healthcare may exist in New Zealand related to age, ethnic group, and rurality. Thirty-day survival was significantly increased in patients conveyed directly to a hospital with PCI-capability.